Identification and Characterization of P0 Protein as a Vaccine Candidate Against Babesia divergens, Blood Parasite of Veterinary and Zoonotic Importance - El-Sayed, Shimaa Abd El-Salam; Rizk, Mohamed Abdo; Eldoumani, Haitham; Sorour, Shimaa Sobhy; Terkawi, Mohamad Alaa; AbouLaila, Mahmoud; Igarashi, Ikuo; Sayed-Ahmed, Mohamed Z. (Frontiers in Veterinary Science, 2022)
The molecular identification and antigenic characterization of P0 protein in Babesia divergens (B. divergens), blood parasite of veterinary and zoonotic importance were carried out in this study for use in developing subunit vaccines against B. divergens infection. Recombinant protein encoding P0 (BdP0) was developed in E. coli and its antiserum was generated in mice for further molecular characterisation. Anti-rBdP0 serum had a specific interaction with the corresponding legitimate B. divergens protein, as confirmed by Western blotting and indirect fluorescent antibody tests. ELISA was used to assess the immunogenicity of BdP0 in a group of 68 bovine field samples, and significant immunological reactivity was found in 19 and 20 positive samples of rBdp0 and B. divergens lysate, respectively. The in vitro growth of B. divergens cultures treated with anti-rBdP0 serum was significantly inhibited (P<0.05). Furthermore, after 6 hours of incubation with 2 mg/ml anti-rBdP0 serum, the ability of pre-incubated free merozoites to invade bovine erythrocytes was reduced by 59.88%.The obtained data suggest the possible use of rBdP0 as diagnostic antigen and may serve as a vaccine candidate against babesiosis caused by B. divergens either in animal or human.